The effect of acute fluid consumption following exercise-induced fluid loss on hydration status, percent body fat, and minimum wrestling weight in wrestlers - Cutrufello, P. T.; Dixon, C. B. (The Journal of Strength and Conditioning Research, 2014)
Acute fluid consumption (approximately 1 L) has been shown to reduce urine specific gravity (Usg) among subjects after an overnight fast, yet it is unknown if Usg may be reduced among subjects who have experienced exercise-induced fluid loss. The purpose of this study was to examine the effect of acute fluid consumption on Usg, body mass, percent body fat (%BF), and minimum wrestling weight (MWW) following an exercise-induced fluid loss protocol. National Collegiate Athletic Association coaches' perceptions of the weight certification program (WCP) were also evaluated. Twelve men wrestlers (19.8 ± 1.14 years) were tested prepractice (PRE), postpractice (POST), and 1 hour after consuming 1 L of water (PFC). Percent body fat was measured by skinfolds (SF), air displacement plethysmography (ADP), and multifrequency and leg-to-leg bioelectrical impedance analysis to calculate MWW. Urine specific gravity measurements significantly increased above PRE (1.013 ± 0.006) at the POST (1.019 ± 0.007; p = 0.017) and PFC (1.022 ± 0.008; p = 0.025) assessments; however, POST and PFC were not significantly different (p = 0.978) from one another. The %BF values were similar (p > 0.05) at each assessment point when using SF and ADP. When compared with PRE, MWW significantly reduced at the POST assessment when using SF (67.2 ± 8.4 vs. 65.7 ± 8.2 kg; p < 0.001) and ADP (66.6 ± 9.1 vs. 64.8 ± 9.0 kg; p = 0.001), reflecting the reduction in body mass observed after exercise. Forty-seven National Collegiate Athletic Association coaches completed the questionnaire and 2 central themes emerged: (a) concerns with the 1.5% weight loss plan and (b) wrestlers using strategies in an attempt to circumvent the WCP. Exercise-induced fluid loss followed by acute fluid consumption equal to 1 L was ineffective in reducing Usg.